O conflito entre direitos fundamentais: as dimensões do conflito entre o direito à moradia adequada e o direito ao meio ambiente ecologicamente equilibrado no espaço urbano brasileiro - Machado, Renata Mendes Santa Maria (Universidade do Vale do Rio do Sinos, 2007)
The objective of this dissertation is to study the conflict between the right to housing and the environmental right both in the light of the Brazilian constitutional law and the theory of the fundamental rights. Before considering the constitutional tutelage, we will analyze the process of historic affirmation of the human rights by recognizing the three different dimensions of rights. In our research we will put emphasis on the relevant action of the UN in the formation of the international system of human rights. The right to housing fits in the second dimension of human rights and is consolidated with the advent of the Social State of Law after the Liberal State has been surmounted. The right to the environment was recognized later in the international scene, after the World War II, whose starting point was treaties on the non-use of nuclear weapons. The human rights are announced in the form of social movements before they become part of both the international system and the internal order of States. Thu
Keywords: conflito entre direitos; Constituição Federal; direito à moradia; direito ambiental; direitos fundamentais; espaço urbano; direitos humanos; adequate housing; conflict between rights; environmental protection; environmental right; Federal Constitution; fundamental rights; right to housing; urban environment; human rights; Ciências Sociais Aplicadas